Critical care health professionals' self-reported needs for wellbeing during the COVID-19 pandemic: A thematic analysis of survey responses. Issue 1 (January 2022) - Elliott, Rosalind; Crowe, Liz; Abbenbroek, Brett; Grattan, Sarah; Hammond, Naomi E.
Abstract: Background: Critical care healthcare professionals are a key part of any pandemic response and are at an increased risk for physical and psychological harm, yet their self-reported suggestions to ameliorate the negative effects of pandemics on their wellbeing have rarely been sought. Objectives: The objective of this study was to explore and interpret themes of critical care healthcare professionals' responses to the question 'What do you think could assist your wellbeing during the COVID-19 crisis?' Methods: A descriptive study using an online survey, performed in April 2020, investigating pandemic preparedness and psychological burden during the early stages of the COVID-19 pandemic among critical care professionals was carried out. Informal snowball sampling was used. Thematic analysis of qualitative data from an open-ended survey item was informed by Braun and Clark. Findings: Eighty percent (2387/3770) of respondents completed the open-ended survey. Three themes were generated from the synthesis: adequate resourcing for the role; consistent, clear information, and prioritised communications; and the need for genuine kindness and provision of support for healthcare professional wellbeing. Conclusions: There is merit for considering the perceptions, concerns, and suggestions of critical care clinicians during a pandemic. Suggestions included simple measures to maintain physical and mental health, clear messaging, consistent information, trust in health and political leaders, supportive working environments, specific training, and allowances for personal circumstances. This information is important for health and political leaders and policy makers to implement strategies to reduce the burden associated with delivering care in the context of a pandemic.